Chimeric proton-pumping rhodopsins containing the cytoplasmic loop of bovine rhodopsin. - Kengo Sasaki; Takahiro Yamashita; Kazuho Yoshida; Keiichi Inoue; Yoshinori Shichida; Hideki Kandori (PLoS ONE, 2014)
G-protein-coupled receptors (GPCRs) transmit stimuli to intracellular signaling systems. Rhodopsin (Rh), which is a prototypical GPCR, possesses an 11-cis retinal. Photoisomerization of 11-cis to all-trans leads to structural changes in the protein of cytoplasmic loops, activating G-protein. Microbial rhodopsins are similar heptahelical membrane proteins that function as bacterial sensors, light-driven ion-pumps, or light-gated channels. They possess an all-trans retinal, and photoisomerization to 13-cis triggers structural changes in protein. Despite these similarities, there is no sequence homology between visual and microbial rhodopsins, and microbial rhodopsins do not activate G-proteins. In this study, new chimeric proton-pumping rhodopsins, proteorhodopsin (PR) and Gloeobacter rhodopsin (GR) were designed by replacing cytoplasmic loops with bovine Rh loops. Although G-protein was not activated by the PR chimeras, all 12 GR chimeras activated G-protein. The GR chimera containing the second cytoplasmic loop of bovine Rh did not activate G-protein. However, the chimera with a second and third double-loop further enhanced G-protein activation. Introduction of an E132Q mutation slowed the photocycle 30-fold and enhanced activation. The highest catalytic activity of the GR chimera was still 3,200 times lower than bovine Rh but only 64 times lower than amphioxus Go-rhodopsin. This GR chimera showed a strong absorption change of the amide-I band on a light-minus-dark difference FTIR spectrum which could represent a larger helical opening, important for G-protein activation. The light-dependent catalytic activity of this GR chimera makes it a potential optogenetic tool for enzymatic activation by light.